Ethical Implications of AI in Financial Services: Bias, Transparency, and Accountability - Puneet Chopra, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This article examines the ethical implications of artificial intelligence (AI) in financial services, focusing on issues of bias, transparency, and accountability. As AI adoption in finance grows rapidly, with 85% of institutions now using AI, it brings both tremendous benefits and significant ethical challenges. The article explores how AI can perpetuate biases in lending and credit scoring, the "black box" problem of opaque AI decision-making, and the complexities of establishing accountability for autonomous AI systems. It analyzes strategies for mitigating these issues, including developing interpretable AI models, implementing robust governance structures, and creating industry-specific ethical guidelines. The discussion highlights the critical need for evolving regulatory frameworks and ethical standards to ensure responsible AI use while harnessing its potential to transform financial services.
Keywords: AI in Finance; Ethical Implications; Bias Mitigation; Transparency; Accountability